Symmetry transitions beyond the nanoscale in pressurized silica glass - Zhen Zhang; Zhengcheng Xie; Walter Kob (Proceedings of the National Academy of Sciences, 2025)
Silica is the paradigmatic network glass-former and understanding its response to pressure is essential for comprehending the mechanical properties of silica-based materials and the behavior of silicate melts in the Earth’s interior. While pressure ( P )-induced changes in the short-range structure—particularly the breakdown of tetrahedral symmetry—have been well documented, structural transformations on larger length scales, important for many material properties, remain poorly understood. Here, we numerically investigate the three-dimensional structure of silica glass as a function of compression up to P ≈ 100 GPa. Using a many-body correlation function, we reveal a complex medium-range order: While for P ≲ 10 GPa, one finds tetrahedral, octahedral, and cubic symmetries, the structure at higher P s exhibits alternating cubic and octahedral particle arrangements. The P -dependence of the corresponding structural correlation length displays two distinct maxima, which permits to rationalize the anomalous compressibility of silica. The identified complex structural organization on intermediate range scales is the result of a pressure-and scale-dependent interplay between directional bonding, packing efficiency, and network stiffness. Since these competing effects are common in network glass-formers, the identified three-dimensional medium-range order, and hence the physical properties of the glass, are expected to be universal features of such materials under extreme conditions.